PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN PADA NILAI PERUSAHAAN DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL PEMODERASI - Ni Kadek Cahya Dwi Utami; Nyoman Angga Pradipa; Ni Wayan Lady Andini; Putu Eka Suryadana (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2025)
This research aims to obtain empirical evidence regarding the influence of profitability and company size on firm value and the role of managerial ownership in moderating this influence. The population of this research is property and real estate companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The sampling technique used was purposive sampling technique and a sample of 102 observations was obtained. The data analysis technique used is Moderated Regression Analysis. The results of the analysis provide evidence that, 1) profitability has a positive effect on firm value, 2) company size has a negative effect on firm value, 3) managerial ownership does not moderate the effect of profitability on firm value, and 4) managerial ownership does not moderate the effect of company size on firm value.